Combining Hashing and Enciphering Algorithms for Epidemiological Analysis of Gathered Data - Quantin, C.; Fassa, M.; Coatrieux, G.; Trouessin, G.; Allaert, F. A. (Methods of Information in Medicine, 2008)
Objectives: Compiling individual records coming from different sources is necessary for multi-center studies. Legal aspects can be satisfied by implementing anonymization procedures. When using these procedures with a different key for each study it becomes almost impossible to link records from separate data collections.Methods: The originality of the method relies on the way the combination of hashing and enciphering techniques is performed: like in asymmetric encryption, two keys are used but the private key depends on the patient’s identity.Results: The combination of hashing and enciphering techniques provides a great improvement in the overall security of the proposed scheme.Conclusion: This methodology makes stored data available for use in the field of public health, while respecting legal security requirements.
Keywords: Security; patient identification; encryption; hashing